1986
DOI: 10.1161/01.res.58.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of endothelium-dependent vascular relaxation in cholesterol-fed rabbit by treatment with the calcium blocker PN 200110.

Abstract: SUMMARY. We tested the effects of low doses of a dihydropyridine calcium antagonist, PN 200110, on endothelium-dependent vascular relaxation in rabbits fed a 1% cholesterol diet. The drug was given orally, 1 mg/day, and control rabbits received placebo. Plasma total cholesterol after 10 weeks, was similar in the placebo-and PN 200110-treated groups. The respective values averaged 2140 ± 116 (n = 14; mean ± SEM) and 2012 ± 115 mg/dl (n = 13). In placebo-treated rabbits, sudanophilic aortic lesions covered 52 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(59 citation statements)
references
References 15 publications
4
53
1
1
Order By: Relevance
“…However, the increased body weight pointed to fluid retention as an adaptation to the prolonged exposure to a vasodilator via activation of compensatory neurohumoral systems (Dupuis et al, 1990;Packer, 1990). Yet, it is unlikely that these adaptations could have accelerated the fatty streak formation, as it is not observed with other vasodilator drugs (Habib et al, 1986;Verbeuren et al, 1986a;Sugano et al, 1986;Chobanian et al, 1990). …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the increased body weight pointed to fluid retention as an adaptation to the prolonged exposure to a vasodilator via activation of compensatory neurohumoral systems (Dupuis et al, 1990;Packer, 1990). Yet, it is unlikely that these adaptations could have accelerated the fatty streak formation, as it is not observed with other vasodilator drugs (Habib et al, 1986;Verbeuren et al, 1986a;Sugano et al, 1986;Chobanian et al, 1990). …”
Section: Discussionmentioning
confidence: 98%
“…In spite of the deliberate inclusion of rabbits without hypercholesterolaemia, the modest desensitization to the a,-adrenoceptor agonist, phenylephrine (Habib et al, 1986;Mugge et al, 1991), the increased sensitivity and contractility to 5-HT (Henry & Yokoyama, 1980;Verbeuren et al, 1986b;Wines et al, 1989) and the diminished ACh-induced relaxations (Verbeuren et al, 1986b;Freiman et al, 1986;Habib et al, 1986;Jayakody et al, 1987;Bossaller et al, 1987) confirmed the altered reactivity of arteries with fatty streaks.…”
Section: Fatty Streaks and Vascular Reactivitymentioning
confidence: 97%
“…The enhancement of the vasoconstrictor effect of 5-hydroxytryptamine (5-HT) was among the first of such changes demonstrated experimentally (Henry & Yokoyama, 1980;Shimokawa et al, 1983;Kawachi et al, 1984). Acetylcholine (ACh)-induced relaxation is diminished in atherosclerotic vessels (Freiman et al, 1986, Habib et al, 1986Bossaller et al, 1987a) and this can also be demonstrated angiographically in patients (Ludmer et al, 1986). The present experiments were designed to investigate the effects of ACh and several pressor agents in intact conscious rabbits.…”
Section: Introductionmentioning
confidence: 86%
“…4 Isradipine is the CA that has shown the most promise as an anti-atherogenic agent at a dosage below that which reduces blood pressure. 5 Isradipine-treated, cholesterolfed rabbits developed less aortic atherosclerotic surface involvement (p<0.03) and less aortic cholesterol content (p<0.05) than an untreated group. It is important to note, however, that in this study the cholesterol diet and drug regimen were begun and continued concurrently.…”
mentioning
confidence: 89%